2008
DOI: 10.1519/jsc.0b013e318182029d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breathing Pattern on Arm Coordination Symmetry in Front Crawl

Abstract: This study analyzed the relationship between breathing pattern and arm coordination symmetry in 11 expert male swimmers who performed the front crawl at their 100-m race pace using seven randomized breathing patterns. Two indexes of coordination (IdCP and IdCNP) and a symmetry index (SI) based on the difference of IdCP - IdCNP were calculated. IdCP calculated the lag time between the beginning of arm propulsion on the nonpreferential breathing side and the end of arm propulsion on the preferential breathing si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 13 publications
3
33
1
8
Order By: Relevance
“…Also a longer relative duration of the left arm propulsion was observed, since swimmers presented a left preference breathing side, resulting in asymmetric coordination (Barden et al, 2011). In spite of being carried out only in nonbreathing cycles, Seifert, Chehensse, Tourny-Chollet, Lemaitre, and Chollet (2008) showed that even in this condition, swimmers use a coordination mode similar to front crawl breathing cycles, that is part of their usual repertoire, emphasizing the powerful role of learned breathing laterality. These conclusions were attained even when the swimmer did not need to turn his head to breathe, indicating that unilateral breathing disturbs arm coordination, and that all the stroke key points studied occurred at a later time within the stroke cycle.…”
Section: Inter-subject Coordination Profilingmentioning
confidence: 96%
“…Also a longer relative duration of the left arm propulsion was observed, since swimmers presented a left preference breathing side, resulting in asymmetric coordination (Barden et al, 2011). In spite of being carried out only in nonbreathing cycles, Seifert, Chehensse, Tourny-Chollet, Lemaitre, and Chollet (2008) showed that even in this condition, swimmers use a coordination mode similar to front crawl breathing cycles, that is part of their usual repertoire, emphasizing the powerful role of learned breathing laterality. These conclusions were attained even when the swimmer did not need to turn his head to breathe, indicating that unilateral breathing disturbs arm coordination, and that all the stroke key points studied occurred at a later time within the stroke cycle.…”
Section: Inter-subject Coordination Profilingmentioning
confidence: 96%
“…Yet, all participants were sprint or middle-distance specialists. To minimize the effect of the breathing pattern adopted over years of training, only the swimmers with unilateral breathing were considered (Seifert et al, 2008). Swimmers had, at least, 5 years of competitive experience and did not show shoulder injury, and thus we assumed that kinetic asymmetry would not be attributable to impingement (Yanai & Hay, 2000).…”
Section: Participantsmentioning
confidence: 99%
“…In fact, it appears that different breathing modes (unilateral vs. bilateral) lead to an asymmetrical arm coordination in the front crawl swimming (Seifert et al, 2005), as breathing causes a lateral movement that disturb the body alignment (Lerda & Cardelli, 2003). Trying to clarify this issue, previous studies (Seifert, Chehensse, Tourny-Chollet, Lemaitre, & Chollet, 2008;Seifert et al, 2005;Tourny-Chollet, Seifert, & Chollet, 2009) showed that handedness, breathing laterality and breathing pattern commonly used, have an effect both in force and coordination symmetry. Experiments aiming to examine how those asymmetries affect swimming performance could help to clarify the swimming science community about the amount of asymmetry that may be considered acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies should include data about body height and weight, body fat and other 55,56 . Furthermore, data about training strategies to improve swimming techniques 47,48,[57][58][59][60][61] to optimise recovery phases 18,62 and warming-up phases 63,64 which have an effect on swimming performances were not registered. Information about motivation and goal orientation was not recorded.…”
Section: Limitationsmentioning
confidence: 99%